Challenges for Implementing the Independent Curriculum (Kurikulum Merdeka): An Analysis of Facilities and Infrastructure Inequality at Madrasah Ibtidaiyah Al-Ishlah Palembang - Irsan Hadi; Assha Laurend Putri Sriwidjaya; Jirniati (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to analyze disparities in facilities and infrastructure as the primary challenges for implementing the Merdeka Curriculum at Madrasah Ibtidaiyah (MI) Al-Ishlah Palembang.​​ the research employs a descriptive qualitative approach through interviews with Islamic Education teachers and direct observations of the school’s physical conditions, including classrooms, the library, sanitation facilities, and technological equipment. The findings indicate that limited classroom space, inadequate sanitation facilities, and insufficient information technology devices have a direct impact on the implementation of differentiated learning, P5RA projects, and technology-based instruction. Additionally, the implementation of two-session learning due to space constraints will impacts the effectiveness of study time. The research findings confirm that insufficient facilities and infrastructure are an essential obstacle to achieving the Independent Curriculum's objectives. Therefore, efforts to strengthen facility and infrastructure management, ensure sustainable funding support, and foster collaboration among schools, government, and the community are required to optimize the quality of learning.